Cost effective sludge reduction using synergetic effect of dark fenton and disperser treatment. (10th January 2019) - Rajesh Banu, J.; Godvin Sharmila, V.; Gayathri devi, M.; Adish Kumar, S.; Kumar, Gopalakrishnan; Nguyen, Dinh Duc; Dattatraya Saratale, Ganesh
Abstract: The proposed work intended to improve sludge reduction efficiency of dark Fenton (DF) treatment. Dark Fenton reduces 61% of sludge in 90 min under the optimized Fe (II) and H2 O2 dosage of 0.008 g/g suspended solids (SS) and 0.032 g/g SS respectively at pH 3. Combination of dark Fenton with disperser (DFD) reduces time required for the treatment from 90 to 30 min with the disperser specific energy input of 835.536 kJ/kg total solids (TS). At 30 min reaction time, mixed liquor suspended solids and total chemical oxygen demand reduction were found to be 65% and 60%, respectively for DFD. The efficiency of DFD treatment revealed best fit with R 2 value of 0.989 during pseudo first order kinetic analysis. The synergistic effect of DFD resulted in 29% higher MLSS reduction and 31% higher TCOD reduction than dark Fenton (DF) in 30 min treatment as the obtained MLSS and TCOD reduction at 30 min treatment time was observed to be 65% and 60% in DFD and 36% and 29% in DF, respectively. Although, DFD demands higher energy input (233.69 kWh), it had potency to reduce higher solids concentration in a short duration and this results in a net profit of 12.852 USD/ton of sludge. Graphical abstract: Image 1 Highlights: Optimum dosage of dark fenton reaction was 0.008 g/g SS and 0.032 g/g SS. Dark fenton with disperser reaction induces maximum reduction in 30 min. 65% of SS reduction obtained during Dark fenton with disperser treatment. The proposed method results a net profit of 12.852 USD/ton of sludge.